Preparo de biocarvões obtidos a partir da biomassa de casca de pinhão para sorção de espécies de cromo em solução aquosa. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
Metallic species can be considered essential nutrients or toxic agents depending on their content and the way they are found in the environment. Metallic species even at low concentrations can cause harmful effects on aquatic biota, and transfer to the trophic chain can also occur. The metallic species under study in this research work are the soluble compounds of chromium in its most stable forms such as the trivalent chromium Cr (III), found as aquocomplexes (Cr (H2O)6 3+), and in the hexavalent form Cr (VI), generally found in their anionic forms CrO4 2- , HCrO4 - and Cr2O7 2- , depending on the concentration of the chromium ion and the pH of the medium in which it is found. The process used to remove the chromium species present in aqueous solution was the sorption process, which is the main objective of the project, to evaluate the sorption capacity of the Cr (III) and Cr (VI) species in different biosorbents obtained from of the biomass of the pinhão bark, seed of Araucária angustifólia, a conifer common in the south and southeast regions of Brazil. The biomasses went through a cleaning process with ultrapure water and after drying they were ground, sieved on a 16 mesh screen and homogenized by quartering. The separated parts were used without previous treatment (B), after acid treatment with HNO3 (BH), after basic treatment with NaOH (BOH), after heat treatment by pyrolysis processes (biochar) at 650 ° C (BC6) and 800 ° C (BC8) and also with chemical activation with ZnCl2 after the pyrolysis (BCA6) and (BCA8) processes. The sorption processes were evaluated by batch, with agitation and controlled temperatures with separation of metallic species in an initial concentration of 50µg L -1 . The levels of chromium that were not absorbed were determined in the supernatant using Atomic Absorption Spectroscopy with Electrothermal Atomization in Graphite Furnace (GFAAS). The most efficient biosorbents for the removal of Cr (III) and Cr (VI) species were the biochar produced at 800 ° C (BC8), which showed a 78 ± 8% removal for Cr (III) and the biochar produced at 800 ° C with chemical activation by ZnCl2 (BCA8), showing a removal of 99.7 ± 0.6% for Cr (VI), much higher than biomass without treatment (B), which was 17.4 ± 15% for Cr (III) and 15 ± 8.5% for Cr (VI). After the sorption processes, characterizations were performed by techniques such as Molecular Spectroscopy in the Infrared Region, X Ray Diffraction, Thermogravimetry, BET Surface Area, Zeta Potential, SEM-FEG Microscopy, only for the starting material, in this case the untreated biomass and the most efficient biosorbents in the sorption process for Cr (III) and Cr (VI). We can observe the improvement in the sorption capacity of the chromium species in all treatments used, with selective improvement with the biosorbents prepared after heat treatment and chemical activation after heat treatment. The increases in the removal of chromium species may be related to changes in the structure of the materials after the treatments, such as the increase in the surface area of the biosorbents as well as the change in the electrical charge on their surface, which helped in the selectivity of the species with negative or positive charge for its electrostatic attractions.
Keywords: Biochar; Biocarvão; Sorção; Cromo; Biochar; Sorption; Chromium; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA